Wrinkling prediction, formation and evolution in thin films adhering on polymeric substrata. (February 2020) - Cutolo, A.; Pagliarulo, V.; Merola, F.; Coppola, S.; Ferraro, P.; Fraldi, M.
Abstract: Wrinkling has recently attracted an increasing interest by suggesting a number of unforeseeable applications in many emerging material science and engineering fields. If guided and somehow designed, wrinkles could be in fact used as an alternative printing way for realizing complex surface geometries and thus employed as an innovative bottom-up process in the fabrication of nano- and micro-devices. For these reasons, the prediction of wrinkles of films adhering on flat as well as on structured substrata is a challenging task, genesis and development of the phenomenon being not yet completely understood both when thin membranes are coupled with soft supports and in cases where the geometry of the surfaces are characterized by complex three-dimensional profiles. Here we investigate the experimental formation of new intriguing and somehow unforeseeable wrinkled patterns achieved on periodic structures, by showing prediction through a new hybrid analytical-numerical strategy capable to overcome some common obstacles encountered in modeling film wrinkling on flat and 3D-shaped substrata. The proposed approach, which drastically reduces the computational effort, furnishes a helpful way for predicting both qualitative and quantitative results in terms of wrinkling patterns, magnitude and wavelength, by also allowing to follow the onset of film instabilities and the progressive evolution of the phenomenon until its final stage. Graphical abstract: Unlabelled Image Highlights: We investigated the experimental formation of wrinkled patterns achieved on periodic structures; Different parameters (substrates, coating metals and shapes) have been analysed; Hybrid analytical-numerical strategy for predicting the onset, evolution of wrinkling in metal film on 3D-shaped substrates. The results might be helpfully utilized for predicting hierarchical organizations of wrinkle patterns